An Evaluation of the Process of Implementation of the Philippine College of Physicians’ Outcome-Based Education Competency-Based Training Program at Vicente Sotto Memorial Medical Center - Librado, Dax Ronald; Tolod, Lourdes; Gawahan, Rogelio (Journal of Interdisciplinary Perspectives, 2025)
In 2019, the Philippine College of Physicians (PCP) launched the Outcome-Based Education- Competency-Based Training Program (OBE-CBTP) in Internal Medicine for implementation in hospitals providing Internal Medicine training. Vicente Sotto Memorial Medical Center (VSMMC) adopted this program the same year, but no prior studies have evaluated its implementation. This study aims to assess the OBE-CBTP implementation process at VSMMC, as perceived by third-year resident physicians and the training core faculty. Data was collected through two sets of questionnaires distributed to third-year residents and the training core faculty, focusing on eight program outcomes, their associated learning objectives, teaching-learning activities, and assessment tasks. Results showed that both groups rated the implementation of the eight program outcomes as Very Highly Implemented. Resident physicians specifically rated the learning objectives as Very Highly Implemented, while teaching-learning activities received ratings of Very Highly Implemented and Highly Implemented, and assessment tasks were rated as Very Highly Implemented. Importantly, no significant differences in evaluations were found based on age, sex, or the type of curriculum from which the residents graduated. Similarly, training core faculty ratings did not show significant variation when analyzed by age, sex, and years of practice, providing insufficient statistical evidence to reject the null hypothesis. The study highlights the successful implementation of an outcome-based education (OBE) approach in the training of Internal Medicine residents at VSMMC, focusing on specific competencies expected at each training level. Participants affirmed that the practice of the Philippine College of Physicians’ Outcome-based Education Competency-Based Training Program (PCP- OBE-CBTP) is effective, serves as a model for others, and has yielded excellent results in training internists. In conclusion, the findings underscore the PCP-OBE-CBTP program's critical contribution to enhancing postgraduate medical education and practice in the Philippines. It is recommended to conduct further studies in other hospitals with similar residency training programs to validate these findings.